STUDENTS’ PERCEPTION OF THE INFLUENCE OF FREE WRITING HABITS IN THESIS WRITING - Syarifa Suraiya Rahmani; Syafiqa Zayyani Wliaratu (IKIP Siliwangi, 2024)
This study explores students' perceptions regarding the impact of free writing habits on their thesis writing process. The study specifically focuses on the concept of free writing, an approach that promotes unrestricted expression and the exploration of spontaneous ideas. The participants include active students working on their theses at the University of Mataram, particularly those in the crucial phase of thesis development. The research employs descriptive qualitative research methods, including questionnaires and interviews. The study analyzes students' feedback on various aspects of free writing. Results indicate positive perceptions, with the majority agreeing that free writing aids idea generation, proposal development, and overall writing skills. Interviews further highlight the technique's effectiveness in overcoming writing challenges. The results highlight the importance of educators endorsing and promoting the development of students' free writing habits, fostering creativity, and enhancing their overall writing proficiency. Educators must encourage the adoption of such practices for an enriched academic experience.